Theoretical Welfare Cost Analysis to Reduce Carbon Dioxide Emissions - Anton Abdulbasah Kamil (Program Studi Statistika Unisba, 2008)
This paper focuses on insurance against the small probability of causing really catastrophic climatechange may justify significantly curbing CO2 emissions. Such extreme non-linearities maybe exist.However predicting future global climate changes is extremely hazardous, and no-one can rule outthe possibility of surprise. This paper uses indirect method to get the possible scenarios that couldoccur, nor what costs or subjective probabilities to attach to most of the catastrophes that have beensuggested.